Enhancing english speaking skills through video project-based learning: a study of Fakfak State Polytechnic students' experiences - Magfirah, Titing; Arridha, Riyadh (Institute of Computer Science (IOCS), 2025)
In Indonesia, English is taught as a foreign language, and among four skills in English learning, speaking is a vital skill for communication. Teachers need to apply effective strategies and select suitable learning models when planning speaking lessons. The chosen model should align with the learning objectives and content to encourage active student participation and improve their speaking skills. Implementing the right learning model is essential to enhance students' speaking performance. This study investigates the experiences of non-EFL students in creating English-speaking video projects within a Project-Based Learning (PBL) framework at Fakfak State Polytechnic, using a descriptive qualitative method. The topic “A Day in My Life” was found to be engaging, though students faced internal and external challenges such as limited vocabulary, pronunciation and grammar errors, difficulty expressing ideas, distractions, and technical issues. Despite these obstacles, the project helped students improve their vocabulary, grammar, pronunciation, confidence, and overall speaking skills in English. This study enriches language education research by presenting evidence that Project-Based Learning (PBL) effectively improves the speaking abilities of non-EFL students. In contrast to conventional approaches that focus on grammar drills and memorization, PBL encourages meaningful language use through practical tasks.